If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7x+2=2(3x-4)x-10
We move all terms to the left:
7x+2-(2(3x-4)x-10)=0
We calculate terms in parentheses: -(2(3x-4)x-10), so:We get rid of parentheses
2(3x-4)x-10
We multiply parentheses
6x^2-8x-10
Back to the equation:
-(6x^2-8x-10)
-6x^2+7x+8x+10+2=0
We add all the numbers together, and all the variables
-6x^2+15x+12=0
a = -6; b = 15; c = +12;
Δ = b2-4ac
Δ = 152-4·(-6)·12
Δ = 513
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$
The end solution:
$\sqrt{\Delta}=\sqrt{513}=\sqrt{9*57}=\sqrt{9}*\sqrt{57}=3\sqrt{57}$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(15)-3\sqrt{57}}{2*-6}=\frac{-15-3\sqrt{57}}{-12} $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(15)+3\sqrt{57}}{2*-6}=\frac{-15+3\sqrt{57}}{-12} $
| 3(2x-3)+4(x+5)=8 | | 1. 8x+2=4x+10 | | -2/7*v=-10 | | 13s-83=4s+7 | | 4(2x-5)=6 | | 10h-47=6h-43 | | 5v-4=10v-84 | | 2x÷4=5x | | -4(x-2)=-3 | | (100)2/10=x | | x2-3x=1 | | 4x-1=3(x+1)x= | | 5z(z+2)(z−1)=0. | | 3^2x+1=212 | | f/17=5 | | W^2+7=y | | Y-8y-9y=10 | | 3y/7+17=37 | | 2a-15=25,a= | | 11b-1=14b-19 | | (D^4)y=0 | | 2a+36=4a | | 4(x+2)-4x=2(4x+9) | | 11x^2-9x-54=0 | | 8^5x+6=710 | | 5(2x-7)=72 | | 25u+87=59u-15 | | z/11=5 | | -6x-18=16 | | 4x-8=3(x-4 | | x=4x36 | | 25^x-2=125 |